Upcoming SlideShare
×

Like this presentation? Why not share!

# Ml lesson 4 2

## on Oct 09, 2011

• 156 views

### Views

Total Views
156
Views on SlideShare
156
Embed Views
0

Likes
0
0
0

No embeds

### Report content

• Comment goes here.
Are you sure you want to

## Ml lesson 4 2Presentation Transcript

• Objective - To graph linear equations using x-y charts. 1 2 4 5 7 2 2 One Variable Equations Two Variable Equations 2x - 3 = 11 +3 +3 2x = 14 x = 7 One Solution Two Solutions x + y = 5 Solutions: x = 1, y = 4 x = 2, y = 3 x = 4, y = 1 x = 5, y = 0 x = 7, y = -2 Ordered Pairs (x,y) (1,4) (2,3) (4,1) (5,0) (7,-2) x y 4 3 1 0 -2 Infinite Solutions
• State whether the given point is a solution to 3x - y = 5. 1) (2, 1) 2) (4, 5) 3) (-3, -14) 4) 5) (-1, 2) 3(2) - 1 = 5 Yes 3(4) - 5 = 5 No 3( - 3) - - 14 = 5 Yes Yes 3(-1) - 2 = 5 No
• Complete the chart and graph. y = 2x - 3 x y -3 -2 -1 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 -1 1 3 x y
• Complete the chart and graph. y = 2x - 3 x y -3 -2 -1 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 -1 1 3 x y
• Complete the chart and graph. y = 2x - 3 x y -3 -2 -1 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 -1 1 3 x y
• Complete the chart and graph. y = 2x - 3 x y -3 -2 -1 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 -1 1 3 x y
• Complete the chart and graph. y = 2x - 3 x y -3 -2 -1 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 -1 1 3 x y
• Complete the chart and graph. y = 2x - 3 x y -3 -2 -1 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 -1 1 3 This line represents all real solutions to y = 2x - 3. x y
• 1) 2x + y = 5 2) - x + 2y = - 4 - 2x - 2x y = - 2x + 5 + x + x 2y = x - 4 2 2 Solve the following equations for y. (Function Form)
• 3) 3x + 5y = 10 4) - 2x + 3y = - 6 - 3x - 3x 5y = - 3x + 10 5 5 + 2x + 2x Rewrite the equation in function form. 3y = 2x - 6 3 3
• Solve the equation for y, complete the chart, and graph. 1) 3x + 2y = 4 - 3x - 3x 2y = - 3x + 4 2 2 x y -4 -2 0 2 4 6 8 5 2 -1 -4 -7 x y
• Rewrite in function form, complete the chart, and graph. 2) x - 3y = 6 - x - x -3y = - x + 6 - 3 - 3 x y -6 -3 0 3 6 9 -4 -3 -2 -1 0 1 x y
• Solve the equation for y, find at least five solutions, and graph. 3) x + 2y = 8 - x - x 2y = - x + 8 2 2 x y -4 -2 0 2 4 6 6 5 4 3 2 1 x y